2018
DOI: 10.4274/meandros.79664
|View full text |Cite
|
Sign up to set email alerts
|

Nitrous Oxide Effects the Uptake of Sevoflurane to the Body During Induction

Abstract: ÖzAmaç: İnhalasyon indüksiyonu sırasında azot protoksit gazının (N 2 O) sevofluranın vücuda alınması sürecinin hızı ve kalitesi üzerindeki etkilerini araştırmaktır. Gereç ve Yöntemler: Jinekolojik müdahale yapılması planlanan Amerikan Anestezistler Derneği kriterlerine göre I-II grubunda 84 kadın hasta randomize edilerek iki gruba ayrıldı. Tek soluk indüksiyonu yöntemi ile anestetize edilen hastalarda birinci gruba [Grup sevoflurane and azot protoksit (SA)] indüksiyonda %8 sevofluran, %67 azot protoksit ve %33… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Thus, reduce the concentration of volatile anaesthetic required to produce the same effect. 13 Many studies have shown the interaction between Sevoflurane and nitrous oxide. Some studies supported the use, while others failed to find any advantage of using nitrous oxide.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, reduce the concentration of volatile anaesthetic required to produce the same effect. 13 Many studies have shown the interaction between Sevoflurane and nitrous oxide. Some studies supported the use, while others failed to find any advantage of using nitrous oxide.…”
Section: Discussionmentioning
confidence: 99%